Uncut Esophagojejunostomy with Double Jejunal Pouch: An Alternative Reconstruction Method that Improves the Quality of Life of Patients after Total Gastrectomy - Jia Qing Gong; Yong Kuan Cao; Guo Hu Zhang; Pei Hong Wang; Guo De Luo (Journal of Investigative Surgery, 2017)
Background: Currently, there is no optimal digestive tract reconstruction technique well recognized by scholars after total gastrectomy. In this study, a new reconstruction method, which is modified from the classic Roux-en-Y procedure, an uncut jejunal esophageal anastomosis with double jejunal pouch (UJEA-DJP) was established, and its advantages for improving the quality of life of patients who undergo total gastrectomy were analyzed. Methods: Altogether 160 patients with gastric cancer enrolled in our center from September 2009 to March 2012 received radical D2 total gastrectomy. According to the reconstruction methods used, these patients were divided into three groups: UJEA-DJP (n = 63), Roux-en-Y (n = 45), and P-loop with Roux-en-Y esophagojejunostomy (P-RY; n = 52). The operation time for reconstruction, complications, prognostic nutritional index (PNI), and the Visick classification among the three groups were analyzed. Results: We found that UJEA-DJP has advantages over Roux-en-Y and P-RY regarding the time of digestive tract reconstruction, incidence rates for long-term complications, postoperative nutritional index, body weight recovery, and the Visick classification for subjective feelings (p < .05). Conclusions: The UJEA-DJP surgical procedure has the advantages of intestinal continuity and double-pouch construction, which can significantly reduce long-term complications and improve the long-term quality of life of patients after surgical procedure.